ANALISIS POLA PERJALANAN ORANG DI KOTA PANGKALPINANG - Firdaus, Ormuz; Gunawan, Indra (SIPIL, 2013)
The vast development of construction is Pangkalpinang City has implicated the rapid growth of population, labor, economy, facility and infrastructure, industries, trading, and tourism has brought a great impact on mobility, which means the increase of time and cost of commuting in the traffic system. An analysis of commutation patterns in Pangkalpinang City is conducted using household interview survey or questionnaires and average daily traffic survey on the roads including secondary data needed in this study. Daily commuting pattern in a city is the combination of work, education, shopping, and schooling commuting pattern. Based on the analysis of the commuting characteristic of people in Pangkalpinang City, it is known that the life standard of most Pangkalpinang people has gotten better economically. This is shown in the increase of household income percentage between Rp 1.500.000 â Rp 2.000.000/month with a composition of workers dominating the number of students. In their daily commuting, most people 75,86% ride motorcycles. This number rises every year, higher than other types of vehicles such as cars (11,78%). The matrix of origin-destination shows that travels between the same origin-destination zone dominates in one district. The area with the highest same origin-destination commutation is Rangkui, and the lowest is Pangkalbalam. This suggests that the commutations done by most of Pangkalpinang residents is still in relatively close range. Â Key Words:Â Mobility, Survey, Commutation